Forensic civism: articulating science, DNA and kinship in contemporary Mexico and Colombia - Ernesto Schwartz-Marin; Arely Cruz-Santiago (Human Remains and Violence, 2016)
The article will present the findings of ethnographic research into the Colombian and Mexican forensic systems, introducing the first citizen-led exhumation project made possible through the cooperation of scholars, forensic specialists and interested citizens in Mexico. The coupling evolution and mutual re-constitution of forensic science will be explored, including new forms of citizenship and nation building projects – all approached as lived experience – in two of Latin America‘s most complex contexts: organised crime and mass death.